Modeling and simulation on starting resistance of a DC motor using MATLAB/SIMULINK / Muhammad Zamri Ramli - Ramli, Muhammad Zamri (2003)
This thesis presents a modeling and simulated results of the starting resistance of a dc motor. In this project, I shall examine the starting transient of a shunt dc motor. The objectives are to implement the SIMULINK simulation of a dc motor operation in modeling the maximum stating current of 100 A and minimum starting current of 60A. The simulation measured at variations of load as at no-load, full-load, half-load and quarter-load conditions. This includes the study of dynamic mathematical modeling of a dc motor. The value of resistance will determine its suitability. Matlab/Simulink software is used in modeling and simulating the starting resistance of a dc motor.